The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1017/s1464793105006937
|View full text |Cite
|
Sign up to set email alerts
|

Direct cell–cell communication: a new approach derived from recent data on the nature and self-organisation of ultradian (circahoralian) intracellular rhythms

Abstract: Recent data concerning ultradian (circahoralian) intracellular rhythms are used to assess the biochemical mechanisms of direct cell-cell communication. New results and theoretical considerations suggest a fractal nature of ultradian rhythms and their self-organisation. The fundamental and innate nature of these rhythms relates to their self-similarity at different levels of cell and tissue organisation. They can be detected in cell-free systems as well as in cells and organs in vivo. Such rhythms are a means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 147 publications
(151 reference statements)
0
18
0
Order By: Relevance
“…[The last mentioned of these have also been called 'minute-order rhythms' (Corner et al, 2002Habets et al, 1987), 'super, c.q., big bursts' (Madhavan et al, 2007;Wagenaar et al, 2006a,b), or 'metastable state transitions' (Sasaki et al, 2007).] Suspected oscillations of still lower frequency, from >5 min up to $24 h, such as are known to exist the intact brain -designated as, respectively, 'tonic/phasic' (Corner, 1990;Orem, 1996;Takahara et al, 2002;Wehrle et al, 2007), 'circahoral' (Brodsky, 2006;Stupfel and Pavely, 1990), 'ultradian' (Corner, 1977;Lavie and Kripke, 1981) and 'circadian' (Dijk and von Schantz, 2005;Mirmiran et al, 1995Mirmiran et al, , 2003 rhythms -can be observed intermittently in longterm neocortical registrations from in vitro neocortex tissue (unpublished observations; also Van Pelt et al, 2004a,b;Wagenaar et al, 2006a) but seem not yet to have been systematically investigated. Fluctuations on the order of several hours have been noted for spontaneous motility in amphibian tadpoles (see Corner, 1977), so that this intermediate periodicity range between an hour ('circahoralian': see Brodsky, 2006) and a day ('circadian') deserves closer investigation.…”
Section: Methodology For Single Channel Time-series Analysismentioning
confidence: 99%
“…[The last mentioned of these have also been called 'minute-order rhythms' (Corner et al, 2002Habets et al, 1987), 'super, c.q., big bursts' (Madhavan et al, 2007;Wagenaar et al, 2006a,b), or 'metastable state transitions' (Sasaki et al, 2007).] Suspected oscillations of still lower frequency, from >5 min up to $24 h, such as are known to exist the intact brain -designated as, respectively, 'tonic/phasic' (Corner, 1990;Orem, 1996;Takahara et al, 2002;Wehrle et al, 2007), 'circahoral' (Brodsky, 2006;Stupfel and Pavely, 1990), 'ultradian' (Corner, 1977;Lavie and Kripke, 1981) and 'circadian' (Dijk and von Schantz, 2005;Mirmiran et al, 1995Mirmiran et al, , 2003 rhythms -can be observed intermittently in longterm neocortical registrations from in vitro neocortex tissue (unpublished observations; also Van Pelt et al, 2004a,b;Wagenaar et al, 2006a) but seem not yet to have been systematically investigated. Fluctuations on the order of several hours have been noted for spontaneous motility in amphibian tadpoles (see Corner, 1977), so that this intermediate periodicity range between an hour ('circahoralian': see Brodsky, 2006) and a day ('circadian') deserves closer investigation.…”
Section: Methodology For Single Channel Time-series Analysismentioning
confidence: 99%
“…In addition, it has been demonstrated that plasmatic concentrations of leptin and adiponectin also present secretion patterns of ultradian pulsatility [20,22]. Ultradian rhythms (fast repetitive oscillations within 20-hour periods) are also a significant part of the organism's temporal organization, allowing more precise adjustment of cellular and tissue responses at optimal time points for best improvement in cellular functions [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The subordination of the mitochondria may represent an echo of past times; it has been suggested that the ancient symbiotic association of a H 2 S-oxidizing bacterium with a H 2 S-producing Archaeal host (35) is perpetuated in today's eukaryotes (36) Evidence from lower eukaryotes (20,26) and animal cells (37,38) indicates that strict temporal separation of events in the ultradian time frame is an archetype and the continuous cultivation of yeast proves perhaps the most-convenient model system for experiments. The period of this ultradian clock varies from one organism to another (is genetically determined); however, the periods observed lie within in the range 30-120 minutes and therefore have sometimes been referred to as circahoralian.…”
Section: Introductionmentioning
confidence: 99%